Education in the Performing Arts in Serbia Between Academic and Self-Education Practices - Milica Ivić (University of Belgrade, 2020)
This paper seeks to situate the question of education in the field of the performing arts within the broader context of the epistemology of art. It looks not only at educational practices and institutions in Serbia today, but also at the dominant theories in this field in a local context. The aim is to present not only the fundamental tendencies and contradictions regarding education in the performing arts, but also the dominant and representative theoretical self-awareness of different actors on the scene. Educational practices in the fields of drama, theatre and other performing arts in Serbia today range from elite academic institutions offering undergraduate, master and doctoral degree studies, to more recent private initiatives, academies and institutes, to unstable collaborative self-education practices on the independent scene. One of the basic starting points of the study is that systems of education, production and presentation in a certain art field are interrelated, and that changes in one of the segments affect other elements in the chain.